The Nature of Work. An Introduction to Dabates on the labour Process - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, " The Nature of Work. An Introduction to Dabates on the labour Process," by Paul Thompson.